‘If I huff and I puff’. Foundations for building Brazil’s image: Evidence from an international systematic review (2001 to 2015) - Mariutti, Fabiana Gondim; Tench, Ralph; Giraldi, Janaina de Moura Engracia; Montanari, Maria Gabriela (Internext, 2017)
The past two decades presents a rapid development of country image research. From the literature, several conceptual frameworks are aligned to specific topics, for instance, country-of-origin, country brand models, socioeconomic changes, among others. Specifically, focusing on Brazil’s image research, this paper provides a systematic review of international articles published between 2001 and 2015. Therefore, this paper concludes that there is not enough research about Brazil’s image, providing an exciting opportunity to advance our knowledge about this complex Latin America country relating to other disciplines. Additionally, most studies have examined Brazil’s image from a ‘tourism’ perspective, followed by ‘exports’ mostly using quantitative methods. This demonstrates that researchers could carry out further research regarding potential theoretical and methodological approaches aligned to other disciplines. Furthermore, the outcomes can orientate new research alignments linked to Brazil’s image and the recent crises (e.g., economic, political, social and ethical).